2019
DOI: 10.3390/w11102136
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Long-Term Water Level Variations in Qinghai Lake in China

Abstract: Qinghai Lake is the largest inland saline lake on the Tibetan Plateau. Climate change and catchment modifications induced by human activities are the main drivers playing a significant role in the dramatic variation of water levels in the lake (Δh); hence, it is crucial to provide a better understanding of the impacts caused by these phenomena. However, their respective contribution to and influence on water level variations in Qinghai Lake are still unclear and without characterizing them, targeted measures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
1
12
0
Order By: Relevance
“…Several studies have stated that the increase in air temperature and decrease in rainfall significantly affect the decrease in lake levels. These phenomena were observed in Qinghai Lake in Qinghai Province, China (Zhang et al 2011;Chang et al 2017;Fang et al 2019), lakes on the Tibetan Plateau (Huang et al 2011;Song et al 2014), Lake Michigan and Lake Huron in the United States (Argyilan and Forman 2003;Hanrahan et al 2010), Lake Superior in the United States (Garcia and Townsend 2016), Lake Sibayi in southern Africa (Nsubuga et al 2019), Lake Dianchi in China (Zhou et al 2014), Lake Urmia in Iran (Arkian et al 2018;Schulz et al 2020;Dehghanipour et al 2020a, b), Lake Issyk-Kul in Kyrgyzstan (Salamat and Abuduwaili 2015;Alifujiang et al 2017), and Lake Dongping in Shandong Province, China (Rong et al 2013). Furthermore, human activities are critical factors affecting decreases in lake levels.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several studies have stated that the increase in air temperature and decrease in rainfall significantly affect the decrease in lake levels. These phenomena were observed in Qinghai Lake in Qinghai Province, China (Zhang et al 2011;Chang et al 2017;Fang et al 2019), lakes on the Tibetan Plateau (Huang et al 2011;Song et al 2014), Lake Michigan and Lake Huron in the United States (Argyilan and Forman 2003;Hanrahan et al 2010), Lake Superior in the United States (Garcia and Townsend 2016), Lake Sibayi in southern Africa (Nsubuga et al 2019), Lake Dianchi in China (Zhou et al 2014), Lake Urmia in Iran (Arkian et al 2018;Schulz et al 2020;Dehghanipour et al 2020a, b), Lake Issyk-Kul in Kyrgyzstan (Salamat and Abuduwaili 2015;Alifujiang et al 2017), and Lake Dongping in Shandong Province, China (Rong et al 2013). Furthermore, human activities are critical factors affecting decreases in lake levels.…”
Section: Introductionmentioning
confidence: 84%
“…Furthermore, global climate change impacts have been observed to affect the water levels of lakes in all countries. For example, Lake Urmia in Iran has experienced a dramatic decline in water levels of approximately 8 m since 1995 (Khazaei et al 2019), and the Qinghai Lake level in China annually decreased by 7 cm from 1956 to 2009 while experiencing an annual increase in air temperature of 0.03 °C (Zhang 2011;Fang et al 2019). Over the past 80 years, the water level fluctuation of Lake Issyk-Kul in Kyrgyzstan occurred due to an increase in temperature from 0.7 to 1.5 °C and a decrease in rainfall of 45-130 mm (Salamat and Abuduwaili 2015).…”
Section: Climate Changementioning
confidence: 99%
“…Climate change and catchment modification induced by human activities are the main drivers, and play a significant role worldwide in the dramatic variation of water levels in lakes. A case study on Qinghai Lake, the largest inland saline lake on the Tibetan Plateau, was presented by Fang et al [30] and the meteorological and land use data collected between 1960 and 2016 have been analyzed to investigate the effect of climate change and human activities on this lake. Results obtained have demonstrated that the water level of Qinghai Lake declined between 1960 and 2004, and since then has risen continuously and gradually, due to changes in evaporation, precipitation, and consequent surface runoff associated with climate changes and catchment modifications.…”
Section: Summary Of This Special Issuementioning
confidence: 99%
“…Hydrological systems are highly sensitive to any changes in the natural environment, and in particular to changes in climatic conditions [1][2][3][4][5]. Processes in catchment areas are shaped by multiple factors that coexist and interact with one another, as well as generating feedbacks.…”
Section: Introductionmentioning
confidence: 99%